George Santayana and emotional distance in philosophy and politics - Laursen, John Christian; Román Alcalá, Ramón (Revista de Filosofía, 2015)
George Santayana (1863-1952) appears emotionally distant and personally uncommitted in many of his writings. In what may have been a related phenomenon, he does not seem to have committed to any school of philosophy, but rather to draw from many of the available schools when it suited him. In this article, we assess his constantly changing use of different philosophies and its implications for both philosophy and politics.